Food product design with Wijaya Kusuma character based on pleasurable design - Waskito, Johan Paing Heru; Wedowati, Endang Retno; Rejeki, Fungki Sri; Wahyuningtyas, Emmy (International Journal of Engineering, Science and Information Technology, 2022)
Understanding and appreciation of the identity of the Universitas Wijaya Kusuma Surabaya with the motto Anggung Wimbuh Linuwih, which means always growing and developing for the better, needs to be done. The strategy that can be applied is to design a superior product that has the character of Wijaya Kusuma This food product was designed with the nuances of the character of Wijaya Kusuma. The product that reviewed in this research is chocolate product. Food product design in this study used the concept of pleasurable design, which reviews product design from the aspects of functionality, usability, and pleasure. Pleasurable design was chosen with the consideration that this product design method involves customers as product users to participate in building product designs as needed and   wanted. The purpose of this study was to determine the attributes of chocolate products according to market demand, as well as to design a chocolate product design with the character of Wijaya Kusuma values. Based on the research results obtained 16 product configurations based on seven product attributes (taste, sweetness level, texture, shape, packaging method, health benefits, and appearance/profile). Attributes that have a high importance value are attributes of appearance/profile and taste. Attributes of appearance/profile can directly describe the character of Universitas Wijaya Kusuma Surabaya. while the taste attribute is one of the key attributes in food products.   Product design 5 (chocolate taste, slightly sweet, texture of slightly hard, rectangle shape, folded packaging method, no preservatives, and UWKS logo profile) became the selected product with a total utility value of 10.75.